Clinical significance and diagnostic value of serum CEA, CA19-9 and CA72-4 in patients with gastric cancer - Liang, Yao (Oncotarget, 2016)
AIMS: To evaluate the clinical significance of multiple serum tumor markers (TMs) in the diagnosis of gastric cancer (GC) and establish an accurate discriminant equation to identify the presence of GC. RESULTS: The serum levels of CEA, CA19-9 and CA72-4 were higher in the GC group than in the control group (P < 0.005). The sensitivity of CEA, CA19-9 and CA72-4 in the diagnosis of GC was 20.1–27.6% individually and increased to 48.2% when they were considered in combination. By using the optimal cut-off value, the sensitivity of CEA, CA19-9 and CA72-4 for the diagnosis of GC was improved but remained unsatisfactory. In addition, we developed the equation Y = −2.185 − 0.015 X1 + 0.180 X2 + 1.226 X3 + 1.505 X4 + 2.749 X5 (X1 = Age, X2 = Sex, X3 =CEA, X4 = CA19-9 and X5 = CA72-4) to predict the presence of GC. This has better accuracy and diagnostic efficiency compared to the combination of TMs. METHODS: Serum carcinoembryonic antigen (CEA), cancer antigen 19-9 (CA19-9)and cancer antigen 72-4 (CA72-4) levels were measured in a total of 2288 patients with GC and 1869 healthy volunteers or patients with benign gastric diseases. We established a diagnostic equation using a portion of the data (training set), and validate its accuracy using the other portion of the data (testing set). CONCLUSIONS: The diagnostic equation increases the accuracy rate for the diagnosis of GC and will be helpful in the clinic.